2019
DOI: 10.3390/nu11081951
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition is Associated with Behavioral and Psychiatric Symptoms of Dementia in Older Women with Mild Cognitive Impairment and Early-Stage Alzheimer’s Disease

Abstract: We examined the nutritional status and its association with behavioral psychiatric symptoms of dementia (BPSD) among 741 memory clinic patients (normal cognition (NC), 152; mild cognitive impairment (MCI), 271; early-stage Alzheimer disease (AD), 318). Nutritional status and BPSD were assessed using the Mini Nutritional Assessment Short-Form (MNA-SF) and the Dementia Behavior Disturbance Scale (DBD), respectively. Compared to subjects with NC, more subjects with MCI and early-stage AD were at risk of malnutrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 57 publications
(58 reference statements)
4
53
0
2
Order By: Relevance
“…Previous studies have shown that high Hdl and Tc levels are positively correlated with the risk of ad (52,53), in contrast to the results of the present study. This may be due to differences in the proportions of patients with moderate to severe dementia in the ad group between the two studies; the severity of ad increases the risk of malnutrition, leading to a decrease in plasma cholesterol levels (54,55). in addition, the results of the present study demonstrated that Hb levels in male patients with ad were reduced, consistent with a previous study which suggested that abnormal Hb levels may result in differences in white matter integrity and cerebral perfusion (56).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that high Hdl and Tc levels are positively correlated with the risk of ad (52,53), in contrast to the results of the present study. This may be due to differences in the proportions of patients with moderate to severe dementia in the ad group between the two studies; the severity of ad increases the risk of malnutrition, leading to a decrease in plasma cholesterol levels (54,55). in addition, the results of the present study demonstrated that Hb levels in male patients with ad were reduced, consistent with a previous study which suggested that abnormal Hb levels may result in differences in white matter integrity and cerebral perfusion (56).…”
Section: Discussionmentioning
confidence: 99%
“…Even mild cognitive decrease can be associated with dietary changes. A study carried out by Kimura et al [33] suggested higher risks of malnutrition among elderly people within early stages of alzheimer compared to cognitively healthy individuals. The relationship between these two conditions is complex.…”
Section: Discussionmentioning
confidence: 99%
“…31 In 1 study, showing that malnutrition is associated with verbal aggressiveness/emotional disinhibition and apathy in MCI and in early stage AD supports the malnutritionneuropsychiatric symptom relationship. 32 Apart from DLB, VaD is the second most common type of dementia that deteriorates nutritional most. Patients with VaD may have poorer health status than other patients with dementia because of the possible underlying cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%